SISTEM INFORMASI PENCATATAN INVENTARIS BARANG PADA BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) KAB. SORONG SELATAN - Nuraida _ Latif; Rohayati - Arifin (STMIK AKBA, 2021)
This study aims to design an information system for recording inventory of goods (SIPIB) at the district disaster management agency. Sorong Selatan is web-based using the Dynamic Systems Development Method (DSDM), which is expected to make it easier for employees to make inventory reports. The application of the Dynamic System Development Method which is expected to facilitate the design of an information system for recording inventory at the BPBD Kab. South Sorong. Data obtained through research in the form of interviews, documentation and literature research. This application uses HTML, CSS, PHP and MySQL as data storage services. The results of this study indicate that SIPIB can be used properly so that the inventory management process is more effective and efficient. Tests carried out in the form of Black Box testing by distributing questionnaires to 30 respondents, namely BPBD office employees and residents of South Sorong Regency who will use this system, resulting in a test value of 64.01%. The system is working fine..